Benzyl isothiocyanate provokes senolysis by targeting AKT in senescent IPF fibroblasts and reverses persistent pulmonary fibrosis in aged mice - Wang, Rui; Yang, Fan; Liu, Ying; Peng, Meiting; Yu, Lu; Hou, Qinhui; Liu, Yuan; Cheng, Zhenshun (Frontiers in Pharmacology, 2025)
IntroductionSenescent cells (SCs) accumulate with age and play a causative role in age-related diseases, such as idiopathic pulmonary fibrosis (IPF). Clearance of SCs attenuates lung fibrogenesis and favors fibrosis resolution, suggesting that targeting of SCs is recognized as a promising therapeutic approach for IPF. Isothiocyanates (ITCs) are natural compounds with anticancer and anti-aging properties, but their role in IPF remains unclear. The aim of our study to investigate whether benzyl isothiocyanate (BITC), a type of ITCs, can act as a senolytic agent thereby attenuating pulmonary fibrosis in aged mice.MethodsPrimary lung fibroblasts from IPF patients and controls were cultured and treated with various ITCs to identify potential senolytic agents. Senescence-associated β-galactosidase staining, Cell viability assays, Annexin V/PI double staining, Caspase 3 activity assay, Western blot analysis, and qPCR were performed to evaluate senescence markers, cell viability, and apoptosis-related proteins after BITC treatment of senescent IPF lung fibroblasts in vitro. HE staining, Masson staining, Hydroxyproline assay, and Western blot analysis were used to assess the pathological progress, collagen content of lung tissues, and fibrotic gene expression changes after BITC treatment in C57BL/6 aged mice.ResultsUsing senescent IPF fibroblasts, we screened and identified BITC as a potent senolytic drug. We show that BITC selectively induces apoptosis in senescent IPF fibroblasts by targeting AKT signal pathway. Intraperitoneal administration of BITC to an age-related lung fibrosis mouse model effectively depleted senescent lung fibroblasts and reversed persistent pulmonary fibrosis.DiscussionOur study reveals that BITC may be a promising therapeutic option for IPF and other age-related disease that progress with the accumulation of senescent fibroblasts.